Amber Finds at Kaup - Kulakov, Vladimir (Archaeologia Lituana, 2016)
Burial ground Kleine Kaup is located in the eastern area of Kaup (currently – southern fringe of the town Zelenogradsk, Northern Sambia) and was discovered on August 3, 1865. Small-scale excavations at the burial ground were carried out by Сarl Engel in 1932. As it transpired from fairly sketchy information from the Berlin Archives about the excavations, 23 Prussian two-layer burials dating back to XI–XIII centuries were unearthed. Since the Prussians mostly used burial custom of cremation at that time, I was not expecting to come across any organic material when I started working at Kleine Kaup in 2008. In the course of the work, it was revealed that the bone plates were preserved with unburned horse remains at the lower burial levels. Besides pieces of amber and items made from amber (beads) with insignificant traces of exposure to fire occurred as mortuary gifts at the upper levels of Prussian burials. However, the most unanticipated amber finds occurred at a grave K52a (excavations of 2011). In the process of unearthing and cleaning a poorly preserved skeleton, polished amber beads of various diametre were found in the area of the skull, practically destroyed by tree roots. To the east of the skull pieces, at the right edge of the lower jaw, fragments of three torded temple rings were found. One of the pieces had a bead on it. To the north-east of it, two pieces of another amber bead were discovered. Thus, it became obvious that the skull of a woman buried in grave K52a was decorated with two pairs of polished amber beads right and left. Moreover, the bead on the right (or both?) was strung on iron temple rings which had hooks for fastening at one end. Direct analogies of the beads from burial site K52a with a specific rhombic cross-section are absent in the archeology of Eurasia. The dating of burial site K52a which, judging by a fragmentary set of jewellery, contains female remains is still problematic. Analogies to this complex should probably be sought in ancientry of Curonians of the Early-Middle Ages who had north-oriented graves and iron torcs and beads.